Peningkatan Keterampilan Proses Sains melalui Penerapan Model Pembelajaran Inkuiri Terbimbing di Kelas XI MIA 2 SMA Negeri Colomadu Karanganyar - Isnaini Fajriah; Marjono Marjono; Sri Dwiastuti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret, 2017)
The research objective was to improve student's Science Process Skill (SPS) through the use of guided inquiry learning model at grade XI MIA 2 of SMA Negeri Colomadu Karanganyar academic year 2015/2016. The research is considered as Classroom Action Research that performed by planning, action, observation, and reflection in each cycle. The subject of research is students of XI MIA 2 SMA Negeri Colomadu Karanganyar that consist of 34 students. Data are obtained by observation, interview, test, and documentation. Data validation used triangulation method. Data were analyzed using qualitative descriptive technique. The research procedure used spiral methods. The result of research showed that application of guided inquiry learning model improved the science process skill of XI MIA 2 SMA Negeri Colomadu academic year 2015/2016. Precentage average of science process skill aspect in pre-cycle is 46,08%, in cycle 1 is 50,71% (improve 4,63%), and in cycle 2 is 61,94% (improve 11,23%). The conclusion of this research describes there was increasing science process skill of student on biology through the application of guided inquiry learning model at grade XI MIA2 in SMA Negeri 2 Colomadu Karanganyar academic year 2015/2016.